Cervical consistency index is a valid predictor of preterm birth in low-risk pregnant women - Pooransari, Parichehr; Salehi, Fatemeh; Afrakhteh, Maryam; Mirzamoradi, Masoumeh; Saleh Gargari, Soraya; Ghatreh Samani, Omid (Universa Medicina, 2018)
Background Preterm birth (PTB) remains a global problem associated with perinatal morbidity, including low birth weight, growth retardation and irreversible damage to the nervous system. The objective of this study was to determine the predictive value of cervical consistency index (CCI) to indicate the occurrence of PTB in mid trimester screening of low risk pregnant women. MethodsThis was a prospective study conducted on low-risk pregnant women at 14-28 weeks of pregnancy. The cervical length (CL) and AP cervical diameter were measured and the CCI determined according to the formula AP2/AP1*100. The ROC curves were drawn according to gestational age and the sensitivity and the specificity were calculated for optimal cut-off for 1st, 5th, 10th, 21th, and 24th centiles of CCI. The inter-observer agreement was validated by interclass correlation coefficients (ICC).ResultsA total of 149 participants were enrolled in this study. Among them, 12.08% had PTB (<37weeks) and 87.92% had normal birth. Mean CCI for all subjects was 68.60%, but was lower in PTB (48.9%). The best cutoff for predicting PTB based on CCI was 59.46% with 99.18% sensitivity and 85% specificity. The AUC for CCI for prediction of PTB <37weeks was 0.936. There was no inter-observer difference in measurement of CCI and CL (ICC values for CCI and CL were 0.997 and 0.990 respectively).ConclusionIn women with normal CL the CCI could predict PTB in the second trimester in low risk women. So, CCI is a valid predictor of PTB in low risk women.